(untitled) (International Journal of Psychosocial Rehabilitation, 2021)
Nanofilms of chromium silicides with thickness of 2-3 nm on surface of diffusion-alloyed monocrystalline silicon are obtained. It is shown, formation of intermediate layer with thickness of 30 mcm between film and volume compensated high-ohm region of crystal. The determined activation energy of the silicidal phase formation process is 1.5